2022
DOI: 10.1007/s13235-022-00460-0
|View full text |Cite
|
Sign up to set email alerts
|

Coalition Formation in Games with Externalities

Abstract: This paper studies an extensive form game of coalition formation with random proposers in games with externalities. It is shown that an agreement will be reached without delay if any set of coalitions profits from merging. Even under this strong condition, the equilibrium coalition structure is not necessarily efficient. There may be multiple equilibria even in the absence of externalities, and symmetric players are not necessarily treated symmetrically in equilibrium. If the grand coalition forms without dela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 83 publications
0
1
0
Order By: Relevance
“…In "Coalition Formation in Games with Externalities", Montero [15] considers partition function games that allow for externalities between coalitions and studies a coalitional bargaining model to determine the coalition structure that will emerge at equilibrium and the division of payoffs among coalition members. It is shown that when the partition function game is positive and fully cohesive, then in any stationary subgame perfect equilibrium of the extensive form game, a coalition structure is formed without delay.…”
mentioning
confidence: 99%
“…In "Coalition Formation in Games with Externalities", Montero [15] considers partition function games that allow for externalities between coalitions and studies a coalitional bargaining model to determine the coalition structure that will emerge at equilibrium and the division of payoffs among coalition members. It is shown that when the partition function game is positive and fully cohesive, then in any stationary subgame perfect equilibrium of the extensive form game, a coalition structure is formed without delay.…”
mentioning
confidence: 99%